36 Inclusion of Different Sources of Ca Salts of Fatty Acids on Productive Responses of Finishing Cattle. (8th March 2022) - Colombo, Eduardo; Cooke, Reinaldo F; Mackey, Shea; Pickett, Autumn; Zylberlicht, Gabriel; Cappellozza, Bruno; Batista, Luis Fernando; Pohler, Ky G; Brandão, Alice
Abstract: This experiment (d -9 to d 148) evaluated productive responses of feedlot cattle consuming or not different sources of fatty acids (Nutricorp, Araras, SP, Brazil) during the finishing period. Bos taurus-influenced steers (n = 120) were ranked by initial body weight (BW; 410 ± 6 kg) on d -9 and allocated to 1 of 20 pens (6 steers/pen) equipped with Calan gate feeders (American Calan, Northwood, NH) for individual feed delivery. Steers within each pen were randomly assigned to receive a corn-based finishing diet containing or not (CON; n = 30) Ca salts of palm oil (PALM, n = 30), Ca salts of soybean oil (SB, n = 30), or a mixture of Ca salts of palm, soybean, and cottonseed oils (MIX, n = 30) at 2% of the diet (as-fed basis). Within each treatment, 12 steers were shipped to a packing plant on d 93 of the experiment, and the remaining steers on d 148 of the experiment. Steer shrunk BW was recorded on d -9 (initial), and final BW calculated as 63% of hot carcass weight. Initial and final BW were used to calculate average daily gain (ADG). Individual dry matter intake was calculated by measuring dietary weekly offer and refusals. Feed efficiency was measured using steer total body weight gain and total dry matter intake during the experiment. No differences were detected for initial BW (P = 0.99). Final BW, BW gain, and dry matter intake were all greater (P ≤ 0.05) for MIX, PALM and CON compared with SB. Feed efficiency was greater (P ≤ 0.05) for MIX and PALM compared with SB, and also greater (P ≤ 0.05) for MIX compared with CON. Longissimus muscle area was greater (P ≤ 0.05) for MIX and CON compared with PALM. Collectively, inclusion of MIX into a finishing diet increased performance and feed efficiency of feedlot cattle, whereas inclusion of SB was detrimental to these responses.